2013
DOI: 10.1371/journal.pntd.0002071
|View full text |Cite|
|
Sign up to set email alerts
|

Placental Histopathological Changes Associated with Plasmodium vivax Infection during Pregnancy

Abstract: Histological evidence of Plasmodium in the placenta is indicative of placental malaria, a condition associated with severe outcomes for mother and child. Histological lesions found in placentas from Plasmodium-exposed women include syncytial knotting, syncytial rupture, thickening of the placental barrier, necrosis of villous tissue and intervillositis. These histological changes have been associated with P. falciparum infections, but little is known about the contribution of P. vivax to such changes. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 42 publications
6
83
1
16
Order By: Relevance
“…Recent reports supported the concept that detection and treatment of pregnant malaria during early gestation prevents miscarriage both in P. vivax and P. falciparum infections [31,43]. At delivery, placental infection by P. vivax has been confirmed both in cases from America and Asia [35,[45][46][47].…”
Section: Dynamics Of Gestational and Placental Malariamentioning
confidence: 88%
“…Recent reports supported the concept that detection and treatment of pregnant malaria during early gestation prevents miscarriage both in P. vivax and P. falciparum infections [31,43]. At delivery, placental infection by P. vivax has been confirmed both in cases from America and Asia [35,[45][46][47].…”
Section: Dynamics Of Gestational and Placental Malariamentioning
confidence: 88%
“…This inflammatory environment in the placenta can affect its anatomic structure and normal function. Thickening of the trophoblast basement membrane, which is likely to impair the normal maternal-fetal nutrient and gas exchange, has been observed in both P. falciparum-infected placentas (32) and Plasmodium vivax-infected placentas (33) and is associated with low birth weight (34). Fibrinoid necrosis was also observed in highly infected placentas (35).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on histopathological analysis of P. vivaxassociated placental lesions 23 concluded that this parasite may induce changes similar to those changes caused by P. falciparum but to a lesser degree of intensity. In that same study, syncytiotrophoblast rupture and syncytial knots as well as fibrinoid deposit and leukocyte infiltrate were observed, and parasitized erythrocytes were found only on P. falciparum infections.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, P. vivax infection does not seem to be associated with placental volume alterations. 25 Although there is little evidence that P. vivax may contribute to the inflammatory process in the intervillous space, 23 it is possible that the increase of placental thickness occurred because of placental inflammation. This possibility would explain, at least in part, changes in the course of pregnancy during acute malaria attacks, such as the occurrence of vaginal bleeding, uterine contraction, loss of amniotic liquid, Data are shown as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%